2023
DOI: 10.1021/acs.energyfuels.3c02230
|View full text |Cite
|
Sign up to set email alerts
|

Design of 3D Metal–Organic Material with Multiple Redox-Active Sites for High-Performance Lithium-Ion Batteries

Abstract: To meet the challenges of poor cycling performance and low specific capacity of organic electrode materials, an example of a three-dimensional manganese-based coordination polymer [Mn 2 (pztc)(H 2 O) 2 ] n (Mn-3D) was synthesized by a simple hydrothermal reaction using a redox-active organic moiety pyrazine-2,3,5,6-tetracarboxylic acid (H 4 pztc) as the linker. The Mn-3D anode material exhibited excellent lithium storage capacity to store 14 lithium ions, with a high theoretical specific capacity of 942 mA h g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The capacity and Coulombic efficiency from the 26th cycle onward tended to remain nearly constant, indicating the good stability and capacity retention of the Fe-CP anode after standing for 5 days. On the basis of the above results, it can be stated that the Fe-CP contains competitive high-performance anode materials in comparison to other typical anode materials in LIBs ( Table 1 ) [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. These findings highlight the exceptional potential of 1D structure materials for lithium storage, offering enhanced performance and reliability for LIBs.…”
Section: Resultsmentioning
confidence: 80%
“…The capacity and Coulombic efficiency from the 26th cycle onward tended to remain nearly constant, indicating the good stability and capacity retention of the Fe-CP anode after standing for 5 days. On the basis of the above results, it can be stated that the Fe-CP contains competitive high-performance anode materials in comparison to other typical anode materials in LIBs ( Table 1 ) [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. These findings highlight the exceptional potential of 1D structure materials for lithium storage, offering enhanced performance and reliability for LIBs.…”
Section: Resultsmentioning
confidence: 80%
“…Liu et al reported a Mn-based MOF encompassing pyrazine-2,3,5,6-tetracarboxylic acid (H4pztc) as the linker via a simple hydrothermal reaction. The organic linker allowed easily accessible sites for the reversible storage of 14 Li ions . Incorporating Mn successfully decreased the energy gap between the organic ligands, leading to improved electrical conductivity.…”
Section: Classification Of Oemsmentioning
confidence: 99%